Salivary Gland Hypofunction and/or Xerostomia Induced by Nonsurgical Cancer Therapies: ISOO/MASCC/ASCO Guideline. Issue 25 (1st September 2021) - Mercadante, Valeria; Jensen, Siri Beier; Smith, Derek K.; Bohlke, Kari; Bauman, Jessica; Brennan, Michael T.; Coppes, Robert P.; Jessen, Niels; Malhotra, Narinder K.; Murphy, Barbara; Rosenthal, David I.; Vissink, Arjan; et al.
Abstract : PURPOSE: To provide evidence-based recommendations for prevention and management of salivary gland hypofunction and xerostomia induced by nonsurgical cancer therapies. METHODS: Multinational Association of Supportive Care in Cancer/International Society of Oral Oncology (MASCC/ISOO) and ASCO convened a multidisciplinary Expert Panel to evaluate the evidence and formulate recommendations. PubMed, EMBASE, and Cochrane Library were searched for randomized controlled trials published between January 2009 and June 2020. The guideline also incorporated two previous systematic reviews conducted by MASCC/ISOO, which included studies published from 1990 through 2008. RESULTS: A total of 58 publications were identified: 46 addressed preventive interventions and 12 addressed therapeutic interventions. A majority of the evidence focused on the setting of radiation therapy for head and neck cancer. For the prevention of salivary gland hypofunction and/or xerostomia in patients with head and neck cancer, there is high-quality evidence for tissue-sparing radiation modalities. Evidence is weaker or insufficient for other interventions. For the management of salivary gland hypofunction and/or xerostomia, intermediate-quality evidence supports the use of topical mucosal lubricants, saliva substitutes, and agents that stimulate the salivary reflex. RECOMMENDATIONS: For patients who receive radiation therapy for head and neck cancer, tissue-sparing radiation modalities should be used when possible to reduce the risk of salivary gland hypofunction and xerostomia. Other risk-reducing interventions that may be offered during radiation therapy for head and neck cancer include bethanechol and acupuncture. For patients who develop salivary gland hypofunction and/or xerostomia, interventions include topical mucosal lubricants, saliva substitutes, and sugar-free lozenges or chewing gum. For patients with head and neck cancer, oral pilocarpine and oral cevimeline, acupuncture, or transcutaneous electrostimulation may be offered after radiation therapy. Additional information can be found at www.asco.org/supportive-care-guidelines .